Off-chain trading for micro grid systems - Marcozzi, Marco; Mostarda, Leonardo; Cacciagrano, Diletta (Frontiers in Blockchain, 2022)
As micro grids and blockchain gained the interest and attention of both academia and the industry, the interaction between the two technologies seems to be inevitable. In this article we present the solutions proposed to enhance micro grids with blockchains, in order to assure a truly decentralized and efficient renewable energy distribution. We discuss the scalability challenges and the opportunities deriving from the off-chaining computing techniques. Lastly, we sketch a design to implement a micro grid-based peer-to-peer local energy market, powered by a off-chain computing protocol called DIVERSITY. Simulating different data logging approaches, it emerges that DIVERSITY allows an actual saving on fee costs and power consumption derived from using a public blockchain platform, such as Ethereum.